Barrita Virus, a novel virus of the patois serogroup (Genus Orthobunyavirus; Family Peribunyaviridae) - Fern?ndez, Diana (American Society of Tropical Medicine and Hygiene, 2020)
During ecological investigations for arboviruses conducted in coastal Chiapas, Mexico, in 2007, isolate MP1078 was obtained from a pool of Psorophora varipes mosquitoes. Based on antigenic characterization, this isolate was classified as a strain of Patois virus (PATV) (Orthobunyavirus genus, Peribunyaviridae family). Recently, we conducted nearly complete genome sequencing of this isolate to gain further insight into its genetic relationship with other members of the Patois serogroup. Based on the genetic characterization, we determined that MP1078 contains S, M, and L genome segments that are genetically distinct from other viruses within the Patois serogroup. Serological analyses confirmed the taxonomic classification of MP1078 as a new virus and species within the Patois serogroup, and we propose the name Barrita virus (BITV).